# Proof of differentiation of Hyperbolic cosine function

$x$ is a variable and the hyperbolic cosine function in terms of this variable is mathematically written as $\cosh{x}$. The differentiation or derivative of $\cosh{x}$ with respect to $x$ is expressed as $\dfrac{d}{dx}{\, \cosh{(x)}}$ in differential calculus. The differentiation of hyperbolic cosine with respect to $x$ can be written in limit form as per the fundamental definition of a derivative.

$\dfrac{d}{dx}{\, f(x)}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{ \normalsize \dfrac{f(x+h)-f(x)}{h}}$

If $f(x) \,=\, \cosh{x}$, then $f{(x+h)} \,=\, \cosh{(x+h)}$. It is time to substitute them to move ahead in deriving the derivative of hyperbolic cosine function with respect to $x$.

$\implies \dfrac{d}{dx}{\, \cosh{x}}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{\cosh{(x+h)}-\cosh{x}}{h}}$

### Express Hyperbolic cosine in exponential form

The hyperbolic cosine functions $\cosh{x}$ and $\cosh{(x+h)}$ are written in terms of exponential terms according to the fundamental definition of hyperbolic cosine.

$\cosh{x} \,=\, \dfrac{e^x+e^{-x}}{2}$

$\cosh{(x+h)} \,=\, \dfrac{e^{(x+h)}+e^{-(x+h)}}{2}$

Now, substitute expansions of hyperbolic cosine functions $\cosh{x}$ and $\cosh{(x+h)}$ in the definition of the derivative of cosine function.

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{\dfrac{e^{(x+h)}+e^{-(x+h)}}{2}-\dfrac{e^x+e^{-x}}{2}}{h}}$

### Simplify the exponential form expression

The exponential form functions are in complex form in the numerator. Now, it is time to simplify it further and it helps us to get the derivative of hyperbolic cosine function in the upcoming steps.

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{\dfrac{e^{(x+h)}+e^{-(x+h)}-e^x-e^{-x}}{2}}{h}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{\dfrac{e^{(x+h)}+e^{-(x+h)}-e^x-e^{-x}}{2}}{\dfrac{h}{1}}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{(x+h)}+e^{-(x+h)}-e^x-e^{-x}}{2} \times \dfrac{1}{h}}$

Multiply both fractions to simplify the function further.

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{[e^{(x+h)}+e^{-(x+h)}-e^x-e^{-x}] \times 1}{2 \times h}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{(x+h)}+e^{-(x+h)}-e^x-e^{-x}}{2h}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x} \times e^{h}+e^{-x-h}-e^x-e^{-x}}{2h}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}e^{h}+e^{-x}e^{-h}-e^{x}-e^{-x}}{2h}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}e^{h}-e^{x}+e^{-x}e^{-h}-e^{-x}}{2h}}$

$e^x$ is a common factor in the first two terms and $e^{-x}$ is another common factor in the next two terms of the numerator. Now, take them common one after one.

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}{(e^{h}-1)}+e^{-x}{(e^{-h}-1)}}{2h}}$

$= \,\,\,$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{1}{2} \times \dfrac{e^{x}{(e^{h}-1)}+e^{-x}{(e^{-h}-1)}}{h}}$

$= \,\,\,$ $\dfrac{1}{2} \times \large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}{(e^{h}-1)}+e^{-x}{(e^{-h}-1)}}{h}}$

$= \,\,\,$ $\dfrac{1}{2} \large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}{(e^{h}-1)}+e^{-x}{(e^{-h}-1)}}{h}}$

$= \,\,\,$ $\dfrac{1}{2} \large \displaystyle \lim_{h \to 0}{\normalsize \Bigg[\dfrac{e^{x}{(e^{h}-1)}}{h}+\dfrac{e^{-x}{(e^{-h}-1)}}{h}}\Bigg]$

The limit of sum of functions can be written as sum of their limits as per sum law of limits.

$= \,\,\,$ $\dfrac{1}{2} \Bigg[\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}{(e^{h}-1)}}{h}}$ $+$ $\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{-x}{(e^{-h}-1)}}{h}}\Bigg]$

$= \,\,\,$ $\dfrac{1}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{x}{(e^{h}-1)}}{h}}$ $+$ $\dfrac{1}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{-x}{(e^{-h}-1)}}{h}}$

The limit of each function is defined as $h$ tends to $0$. So, $e^x$ and $e^{-x}$ are common functions.

$= \,\,\,$ $\dfrac{e^{x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{h}-1}{h}}$ $+$ $\dfrac{e^{-x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{-h}-1}{h}}$

### Find the limit of each function

The expression in mathematical form is simplified successfully. Now, it is time to find the differentiation of hyperbolic cosine function.

$= \,\,\,$ $\dfrac{e^{x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{h}-1}{h}}$ $+$ $\dfrac{e^{-x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{-h}-1}{h} \times \dfrac{-1}{-1}}$

$= \,\,\,$ $\dfrac{e^{x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{h}-1}{h}}$ $+$ $\dfrac{e^{-x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{(e^{-h}-1) \times -1}{h \times -1}}$

$= \,\,\,$ $\dfrac{e^{x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{h}-1}{h}}$ $+$ $\dfrac{e^{-x}}{2}\large \displaystyle \lim_{-h \to 0}{\normalsize \dfrac{-(e^{-h}-1)}{-h}}$

$= \,\,\,$ $\dfrac{e^{x}}{2}\large \displaystyle \lim_{h \to 0}{\normalsize \dfrac{e^{h}-1}{h}}$ $-$ $\dfrac{e^{-x}}{2}\large \displaystyle \lim_{-h \to 0}{\normalsize \dfrac{e^{-h}-1}{-h}}$

According to exponential limit rule, the limit of every function is equal to one.

$= \,\,\,$ $\dfrac{e^{x}}{2} \times 1$ $-$ $\dfrac{e^{-x}}{2} \times 1$

$= \,\,\,$ $\dfrac{e^{x}}{2}-\dfrac{e^{-x}}{2}$

$= \,\,\,$ $\dfrac{e^{x}-e^{-x}}{2}$

$= \,\,\,$ $\sinh{x}$

$\therefore \,\,\, \dfrac{d}{dx}{\, \cosh{x}} \,=\, \sinh{x}$

Therefore, it is proved that the derivative of hyperbolic cosine with respect to $x$ is equal to hyperbolic sine in terms of $x$.

Latest Math Topics
Email subscription
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
###### Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.